Glycol methacrylate-embedding medium to study morphological alterations of saphenous vein under brief and crescent pressurizations - Prado,Cibele M. (2008)
PURPOSE: This study sought to evaluate the efficiency of glycol methacrylate-embedding medium to detect morphological alterations of human saphenous vein submitted to brief and crescent pressurizations. METHODS: Saphenous veins of 20 CABG patients were randomly distributed into four experimental groups (control, 100, 200 and 300 mmHg pressures during 15 seconds). To quantify the percentage of endothelium spread over vein surface a microscope magnification of 100x was used for measurements. Morphometric analysis was performed using videomicroscopy with the Leica Qwin software in conjunction with a Leica microscope, videocamera, and an on-line computer. RESULTS: A slight tendency of quantitative increase was observed in all parameters including percentage of endothelium spread over vein surface and thickness of saphenous vein walls (intima and media layers). CONCLUSIONS: The glycol methacrylate-embedding allowed sections with adequate resolution of structural details and revealed to be an extremely useful method to study pressurized human saphenous veins.